Gasto público en educación superior y su relación con el acceso a la educación técnica y universitaria en el departamento de Loreto 2013–2022 - Leon Alvarado, Soledad Ines (2025)
This study examines the relationship between public spending on higher education and access to technical and university education in the Loreto region of Peru from 2013 to 2022. Using a quantitative approach and a correlational design, variables such as per-student spending, the number of faculty, and the average schooling level of the adult population were analyzed. Findings reveal a positive correlation between public spending and educational access, though the strength of this relationship varies depending on the factors involved. The moderate correlation between per-student spending and the number of faculty highlights the importance of an adequate resource allocation to meet academic demand without compromising educational quality. Additionally, the schooling level of the adult population shows a limited influence on access to higher education, indicating that other socioeconomic factors play a significant role. The research concludes that while public spending positively impacts access, comprehensive policies are needed to ensure stable financing tailored to regional needs. This study provides a foundation for future strategies to promote accessible and high-quality higher education in Loreto.